PENGEMBANGAN SISTEM TUTORIAL BERINTELEGENSIA BERBASISACT-R (Architecture of Cognitive Tutors) UNTUK MENDUKUNG PROSES PEMBELAJARAN PEMROGRAMAN JAVA - Giri Rahayu Bastian, - (2010)
The study, entitled Intelligent Tutoring System Based of ACT-R (Architecture of Cognitive Tutors) to Supporting Java Programming Learning Process identical with a system that was developed and intended for a process of learning problem solving Java programming and acts as a media and supporting systems of learning in it. This study aims to know the carrying capacity of the system and its influence on students learning the Java programming targeted and responses after applying the system. Tutorial system is synonymous with computer-based learning or CAI (Computer Assisted Instruction) developed by the developers of the system becomes ICAI (Intelligent Computer Assisted Instruction or which commonly called the ITS (Intelligent Tutoring System).This study is a development system and accompanied by modeling, followed by testing of trials limited to 20 respondents Vocational High School students, majoring in Software Engineering namely to give students some form of self-evaluation instrument before testing and self evaluation system after system testing. Research to produce changes in the trend view of the system that is 2.50% through self-evaluation test before testing the system and after system testing.